Relationship between the Dispersion of Rubber Particles and the Tensile Behavior in Nylon 6/Modified Butyl-Rubber Blend System - HARA, Yuichi; MOROOKA, Naoyuki; SAWAI, Daisuke; KANAMOTO, Tetsuo; SOEDA, Yoshihiro (KOBUNSHI RONBUNSHU, 2003)
Effect of particle sizes of the rubber component dispersed in a matrix on the tensile behavior was studied for a 60/40 (wt/wt) blend system consisting of nylon 6 (PA 6) and a brominated poly (isobutylene-co-p-methylstyrene) copolymer (BIMS rubber). The size of BIMS particles was controlled by changing the melt-viscosity ratio of PA 6 and BIMS components, using three PA 6′s with different molecular weights. Although the nominal stress/strain curves of the blends at room temperature were identical at a low strain <5%, their differences became more significant with increasing strain and each blend showed a constant stress at a higher strain >10%. This constant stress was lower for a blend consisting of larger rubber particles. SEM observations revealed that the large rubber particles were liable to form cavitation upon elongation, whereas such cavitation was suppressed for the smaller particles. Therefore, the different tensile behaviors of these blends are ascribed to the selective formation of cavities within larger rubber particles upon elongation at room temperature. Such a mechanism for the origin of different tensile behaviors was also supported by the deformation characteristics at elevated temperatures.